The impact of information and communication technology (ICT) based technologies in the teaching and learning at early childhood education level at riverside stimulation centre in Imbizo district in Bulawayo Metropolitan Province. - Ndebele, Mollet (Midlands State University, 2019)
The research focused into the impact of Information and Communication Technology (ICT) based technologies in the teaching and learning at Early Childhood Education (ECE) level settings in the context of the new curriculum in Bulawayo Urban schools. The study was conducted at Riverside Stimulation Centre in Imbizo District in Bulawayo Metropolitan Province. Ten ECE teachers formed the sample. Questionnaires were used to gather information from teachers. Focus groups interviews were used to gather information from ECE parents and guardians. Prior to the new curriculum teaching learners ICT at Early Childhood Education level using their own knowledge without the guidance of policy and structured syllabi. Therefore learners have been vulnerable to a number of risks depending on strength or weaknesses and competency of the ICT teacher. Risks were categorised as physical, social and psychological, affecting the ECE learner. However, the reviewed curriculum with reference to ECE has addressed topical issues via cross-cutting themes such as; Collaboration, HIV &AIDS, Heritage Studies, Human Rights, Child Protection, Gender, Environmental Issues and Disaster Management. The researcher has noted that parents and school administration have not appreciated ICT because they feel it is not an examinable subject as well as the cost of acquiring of ICT devices to facilitate the learning course of ECE learners. On the contrary the ECE learners have received ICT education positively with excitement because it brings new learning dimensions- multi-media experiences; touch, feel, see, these stimulated at one go ( up- to- date visual, audio, and text- based data which is current) as opposed to traditional teaching and learning methods (textbooks that are outdated). The researcher also noted that there is apathy in parents in the ECE activities which greatly affected progress of skills acquisition. There should be a positive relationship between parents, administration and teachers so that parents appreciate the value of ICT competency. Parents play a critical role in developing school interests by their children, that is, a good parent – child relationship yield positively as the child will have interest in his/ her school. The researcher noted that the private sector has a tendency of investing at higher levels of education, that is, tertiary and polytechnic settings and ignores totally the lower levels like ECE. As a result the researcher recommends the private sector to plough back/invest in the education of ICT skills at grass root levels like ECE levels. The researcher recommends the Ministry of Primary and Secondary Education to prioritise giving the necessary and up-to-date skills in ICT teaching and learning. Also MoPSE should play a major role in facilitating schools in acquiring low cost ICT tools such as computers, laptops, tablets, multi-media devices (speakers, cameras) and access to affordable internet.